MEASURER OF THE ATMOSPHERE`S SPECTRAL TRANSPARENCY - Asatryan, R. S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
Optical-electronic measuring complex is described, intended for the operative measurement of atmosphere’s transparency in the wavelengths region of 0.35-1.03 μ and of the meteorological optical range in the different climatically conditions from 0.1 to 300 km. The technique of realization of full-scale measurement of a parameter of atmospheric easing for seen beams (on λ = 0.55 μ ) with sensitivity not worse 3,4⋅10–5 km–1⋅mV–1 is stated.